2011
DOI: 10.3109/02699206.2011.563900
|View full text |Cite
|
Sign up to set email alerts
|

Language assessment of a Farsi–Norwegian bilingual speaker with aphasia

Abstract: The increased occurrence of strokes combined with the high incidence of bilingualism in many regions of the world has led to an increasing number of bilingual adults with aphasia. The literature on bilingual aphasia shows the need for valid, comprehensive and reliable assessment tools for diagnostic and treatment purposes. In spite of a growing number of case studies of bilingual speakers with aphasia, there is still a need for more studies of speakers with different language combinations. This case study desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…A pre‐session briefing was either used or recommended as a strategy in most studies (Jodache et al . , Kambanaros and van Steenbrugge , Knoph , Koumanidi Knoph , Roger and Code ). The pre‐session briefings involved, or were recommended to include: explaining the aim and purpose of the session; going through the assessment materials; explaining the nature of ACDs and how to facilitate good communication with people with ACDs; letting the interpreters know what errors to look out for; and asking interpreters to avoid clarifying questions during assessment sessions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A pre‐session briefing was either used or recommended as a strategy in most studies (Jodache et al . , Kambanaros and van Steenbrugge , Knoph , Koumanidi Knoph , Roger and Code ). The pre‐session briefings involved, or were recommended to include: explaining the aim and purpose of the session; going through the assessment materials; explaining the nature of ACDs and how to facilitate good communication with people with ACDs; letting the interpreters know what errors to look out for; and asking interpreters to avoid clarifying questions during assessment sessions.…”
Section: Resultsmentioning
confidence: 97%
“…Where language(s) spoken was reported, speech pathologist participants were mainly monolingual ( n = 220), compared with only 54 multilingual speech pathologist participants. Five studies reported that the interpreter participants involved were professional interpreters (Kambanaros and van Steenbrugge , Knoph , Koumanidi Knoph , Merlini and Favaron , Roger and Code ), while two survey studies mentioned family members being used as untrained interpreters (Hersh et al . , Roger et al .…”
Section: Resultsmentioning
confidence: 99%
“…Second, bilingual aphasia assessments also need to be matched in difficulty across the two languages to allow an accurate comparison of performance in both languages (Fabbro, 2001a;Kiran & Roberts, 2012;Lorenzen & Murray, 2008;Marrero et al 2002;Mindt et al 2008). This is because in BWA the degree to which one language is impaired may be different from the degree to which another language is impaired (Fabbro, 2001a;Fabbro & Frau, 2001;Koumanidi Knoph, 2011;Lorenzen & Murray, 2008;Paradis, 2001). Furthermore, the two languages may show different trajectories of long-term recovery.…”
Section: Considerations For Bilingual Assessmentmentioning
confidence: 99%
“…2008). This is because in BWA the degree to which one language is impaired may be different from the degree to which another language is impaired (Fabbro, 2001a; Fabbro & Frau, 2001; Koumanidi Knoph, 2011; Lorenzen & Murray, 2008; Paradis, 2001). Furthermore, the two languages may show different trajectories of long‐term recovery.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies investigating language assessment of bilingual individuals with aphasia have tended to use quantitative approaches, measuring language presentation or comparing presentation within each language (Kambanaros & Grohmann, 2011;Kiran & Iakupova, 2011;Koumanidi Knoph, 2011). Recently, researchers have used qualitative approaches to explore the experience of aphasia within a few specific cultures (Armstrong, Hersh, Hayward, Fraser, & Brown, 2012;Legg & Penn, 2013;McLellan, McCann, Worrall, & Harwood, 2013).…”
Section: Introductionmentioning
confidence: 99%